Benzo[a]phenoxazinium chlorides with aliphatic, aromatic and chlorinated terminals in 5- and 9-amino positions: photophyscial characterisation in anhydrous ethanol - Carvalho, Marcello M. T. (2014)
Thanks are due to the Fundação para a Ciência e Tecnologia (FCT, Portugal) for financial support to the NMR portuguese network (PTNMR, Bruker Avance III 400-Univ. Minho), FCT and FEDER (European Fund for Regional Development)-COMPETEQREN-EU for financial support to Research Centres CQ/UM [PEst-C/QUI/UI0686/2013 (FCOMP-01-0124-FEDER-037302)] and CFUM [PEstC/FIS/UI0607/2013 (F-COMP-01-0124-FEDER-022711)]. Post-doctoral grant to B. R. Raju (SFRH/BPD/62881/2009) is also acknowledged to FCT, POPH-QREN, FSE.